2022
DOI: 10.2196/40064
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experience and Feedback After Using an Electronic Health Record–Integrated COVID-19 Symptom Checker: Survey Study

Abstract: Background Symptom checkers have been widely used during the COVID-19 pandemic to alleviate strain on health systems and offer patients a 24-7 self-service triage option. Although studies suggest that users may positively perceive web-based symptom checkers, no studies have quantified user feedback after use of an electronic health record–integrated COVID-19 symptom checker with self-scheduling functionality. Objective In this paper, we aimed to underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…33,101 Other effective features included online screening, medication refills, and appointment scheduling tools, along with decision support for self-care and bidirectional portals for sharing personal health information. [102][103][104][105][106] The use of patient-facing technology generated efficiencies of care and costs savings. Studies noted that greater use of patient-facing technology reduced costs for substance use treatment and decreased missed appointments and emergency room visits.…”
Section: Advanced Patient-facing Featuresmentioning
confidence: 99%
“…33,101 Other effective features included online screening, medication refills, and appointment scheduling tools, along with decision support for self-care and bidirectional portals for sharing personal health information. [102][103][104][105][106] The use of patient-facing technology generated efficiencies of care and costs savings. Studies noted that greater use of patient-facing technology reduced costs for substance use treatment and decreased missed appointments and emergency room visits.…”
Section: Advanced Patient-facing Featuresmentioning
confidence: 99%
“…OSCs may indeed provide patients with a more personalized assessment than search engines such as Google [ 7 ] and can be used to not only get a diagnosis or a triage recommendation without going to a physician but also learn more about the cause of symptoms or better understand a diagnosis [ 8 ]. Studies focused on COVID-19 OSCs showed that these tools tend to have high overall user satisfaction [ 9 ] and can help support remote care and self-management, thus reducing the demands on clinicians and health services [ 10 ].…”
Section: Introductionmentioning
confidence: 99%